2020
DOI: 10.1016/j.jidi.2020.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Imagerie de la pneumonie COVID-19

Abstract: devant une dyspnée aiguë. Les techniques d'intelligence artificielle vont permettre de faire des diagnostics automatiques fiables et de quantifier l'étendue lésionnelle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Although the precise structure of the observed lesions was not taken into account in the study by Mader et al, the extent of opacities was correlated with several patient outcomes including Intensive Care Unit (ICU) length of stay (R = 0.81; p<.001) ( 14 ). Typical findings in COVID-19 include Ground Glass Opacities (GGO) which are often bilateral with a peripheral, posterior and basal distribution ( 15 , 16 ). Adjacent pleura thickening, interlobular septal thickening, and air bronchograms are also common, each occurring in approximately half of cases ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise structure of the observed lesions was not taken into account in the study by Mader et al, the extent of opacities was correlated with several patient outcomes including Intensive Care Unit (ICU) length of stay (R = 0.81; p<.001) ( 14 ). Typical findings in COVID-19 include Ground Glass Opacities (GGO) which are often bilateral with a peripheral, posterior and basal distribution ( 15 , 16 ). Adjacent pleura thickening, interlobular septal thickening, and air bronchograms are also common, each occurring in approximately half of cases ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Crazy paving and consolidation occur later during the course of disease ( 17 , 18 ). Some authors have suggested the existence of pseudo-nodular presentations, which could represent approximately 10% of cases ( 15 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement classically predominates in the peripheral, posterior, and basal regions. Other atypical CT signs appear in the form of pseudonodular condensations, sometimes accompanied by an inverted halo sign [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT involvement of the lungs in SARSCov-2 infection is part of the COVID-19 severity criteria [2]. This chest scan remains the most reliable diagnostic tool due to the often typical images of COVID-19 [3]. It constitutes a prognostic factor in many studies [4].…”
Section: Introductionmentioning
confidence: 99%